Pattern-Matching Toolkit has many applications - Flexible Pattern-Matching in Strings: Practical. On-line Search Algorithms for Texts and Biological Sequences - Mann, C.J.H (Kybernetes, 2003)
"Flexible Pattern-Matching in Strings: Practical. On-line Search Algorithms for Texts and Biological Sequences" by Gonzalo Navarro and Mathieu Raffinot.